Pendampingan Pelaksanaan Santunan Anak Yatim-Piatu pada Peringatan 10 Muharram di Kelurahan Kumai Hilir - Rizki Aan Saputra; Ahmad Firdaus; Muhammad Azhar; Risa Latus Saadah; Rivana Cahya Ramadana; Rista Rofikatul Mujayanah; Rayhanah Rayhanah; Surawan Surawan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to describe and evaluate the accompaniment in the implementation of donations to orphans during the 10th Muharram commemoration in Kelurahan Kumai Hilir, which is an annual tradition with significant social and religious values. The main focus of this study is the effectiveness of the implementation, where there are shortcomings in planning, committee coordination, and the distribution of donations, which are often uneven and not well-targeted. To understand these dynamics, this study uses a descriptive qualitative approach with observation, in-depth interviews, and documentation methods, involving various parties such as the organizing committee, community leaders, and orphans as beneficiaries. The data obtained shows that the accompaniment provided during the donation process successfully improved various important aspects, including active participation of the local community in the event, improvements in the coordination system among the previously unstructured committee, and ensuring that donation distribution became more targeted and fair. In addition to material benefits, the orphans who received donations felt better emotional support, with more attention from the community that was more directly involved in the donation process. This activity also played a role in strengthening social solidarity among residents, making the 10th Muharram commemoration not only a moment for giving donations but also an opportunity to build stronger social ties between the community and the beneficiaries. With this accompaniment, it is hoped that the donation tradition in Kelurahan Kumai Hilir can continue to develop in a more organized manner and have a more significant impact on the well-being of orphans as well as the social life of the community as a whole.